Validity of Letter D in the Certificate Registration Processsystematic Land Ownership Rights in Kudus Regency - Yustinov, Raras Laila (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The implementation of the Complete Systematic Land Registration Program encourages the role of the Regency / City Land Office not only as an institution that produces land title certificates, but also helps land owners to obtain proof of rights and empower land to improve welfare. Various problems also occur in land registration such as incorrect information provided by the applicant, incorrect information provided by the applicant due to the lack of proactivity of the community as applicants to come directly to the land office, asking what are the administrative requirements that must be prepared in the initial process of land registration.